Fast particulate nitrate formation via N2O5 uptake aloft in winter in Beijing - Wang, Haichao; Lu, Keding; Chen, Xiaorui; Zhu, Qindan; Wu, Zhijun; Wu, Yusheng; Sun, Kang (Atmospheric chemistry and physics, 2018)
Particulate nitrate (pNO3-) is an important component of secondary aerosols in urban areas. Therefore, it is critical to explore its formation mechanism to assist with the planning of haze abatement strategies. Here we report vertical measurements of NOx and O3 by in situ instruments on a movable carriage on a tower during a winter heavy-haze episode (18 to 20 December 2016) in urban Beijing, China. Based on the box model simulation at different heights, we found that pNO3- formation via N2O5 heterogeneous uptake was negligible at ground level due to N2O5 concentrations of near zero controlled by high NO emissions and NO concentration. In contrast, the contribution from N2O5 uptake was large at high altitudes (e.g., > 150 m), which was supported by the lower total oxidant (NO2 + O3) level at high altitudes than at ground level. Modeling results show the specific case that the nighttime integrated production of pNO3- for the high-altitude air mass above urban Beijing was estimated to be 50 µg m-3 and enhanced the surface-layer pNO3- the next morning by 28 µg m-3 through vertical mixing. Sensitivity tests suggested that the nocturnalNOx loss by NO3–N2O5 chemistry was maximized once theN2O5 uptake coefficient was over 2 × 10-3 on polluted days with Sa at 3000 µm2 cm-3 in wintertime. The case study provided a chance to highlight the fact that pNO3- formation viaN2O5 heterogeneous hydrolysis may be an important source of particulate nitrate in the urban airshed during wintertime.